Constitutionality issues within the taxation of salaries in Serbia - Kostić Svetislav V. (Anali Pravnog Fakulteta u Beogradu)
This paper deals with the problems which emanate from the lack of respect for the concept of gross salary in the process of drafting tax incentives for employers at the level of salary tax and mandatory social security contributions in Serbia. The author's research shows that such measures are inspired by the widely shared belief that the high burden imposed on employers by virtue of salary tax and mandatory social security contributions on wages is the primary cause of chronic unemployment, wherein he attempts to argumentatively disprove this 'illusion'. The paper illustrates that the tendency of the Serbian legislator, evidenced more than a decade ago, to provide incentives to employers at the expense of the salary with belongs to the employee, is in conflict not only with the demand for the existence of a unified Serbian legal system, but also infringes several rights expressly guaranteed by the Serbian Constitution (right to property, right to social security, right to just compensation), as well as the provision of Art. 1 of the Protocol No. 1 to the European Convention on Human Rights.